2019
DOI: 10.1021/acscentsci.8b00755
|View full text |Cite
|
Sign up to set email alerts
|

How Do Surfactants Control the Agglomeration of Clathrate Hydrates?

Abstract: Clathrate hydrates can spontaneously form under typical conditions found in oil and gas pipelines. The agglomeration of clathrates into large solid masses plugs the pipelines, posing adverse safety, economic, and environmental threats. Surfactants are customarily used to prevent the aggregation of clathrate particles and their coalescence with water droplets. It is generally assumed that a large contact angle between the surfactant-covered clathrate and water is a key predictor of the antiagglomerant performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 104 publications
2
52
2
Order By: Relevance
“…The atomistic simulations by Phan et al [49] also suggested that the surface diffusion of AAs at hydrate-oil interfaces strongly depends on the features of the surfactant headgroup. Also consistent with atomistic simulations [47], Nullage et al [53] showed that dodecane and dodecanol co-adsorb at the hydrate-dodecane interface. For example, at 41% of the full dodecanol monolayer, dodecane intercalation causes the interfacial dodecanoldodecane film to yield an interfacial layer with density ~ 95% that of the crystal.…”
Section: Recent Simulationssupporting
confidence: 68%
See 4 more Smart Citations
“…The atomistic simulations by Phan et al [49] also suggested that the surface diffusion of AAs at hydrate-oil interfaces strongly depends on the features of the surfactant headgroup. Also consistent with atomistic simulations [47], Nullage et al [53] showed that dodecane and dodecanol co-adsorb at the hydrate-dodecane interface. For example, at 41% of the full dodecanol monolayer, dodecane intercalation causes the interfacial dodecanoldodecane film to yield an interfacial layer with density ~ 95% that of the crystal.…”
Section: Recent Simulationssupporting
confidence: 68%
“…These approaches strongly depend on the accuracy of the force fields and on the size of the systems being simulated, with larger systems expected to provide more reliable results because they can account for multiple phenomena occurring simultaneously; benchmarking against both experiments and atomistic simulations is necessary before simulating complex systems using coarse-grained approaches. Naullage et al [53], e.g., recently probed how surfactants could act as AAs using a coarse-grained simulation. The results reinforce the atomistic simulations conclusions, while providing additional insights.…”
Section: Recent Simulationsmentioning
confidence: 99%
See 3 more Smart Citations